The Effect of Motivation, Work Environment, and Workload on Employee Performance at PDAM Tirtauli Pematang Siantar - Niarita Bukit (Green Publisher Indonesia, 2022)
This research aims to examine and analyze the effect of motivation, work environment and workload on employee performance at PDAM Tirtauli Pematang Siantar. The nature of the research in this study is explanatory. The number of samples in this study were 88 samples. The independent variables in this study consisted of motivation (X1), work environment (X2) and workload (X3), while the dependent variable was employee performance. Data analysis used multiple linear regression analysis. The results showed that partially or simultaneously the variables of motivation, work environment and workload had a significant effect on employee performance at PDAM Tirtauli, Pematang Siantar City.